Strategi Penerapan Program Penguatan Pendidikan Karakter Nasionalisme Melalui Program Polisi Cilik di MI - Syaifuddin, Selamet; Ashimuddin, Moh.; Ulfa, Khuizzanul; Prasetyo, Ma’ruf Hendrawan; Samara, M. Iqbal Rizqi Farihat; Sa'adah, Siti Fatimatus; Sunadi, Sunadi (Journal of Elementary Education Research, 2024)
This study describes the implementation strategy of the Nationalism Character Education Strengthening Program through the “Pocil” (Little Police) Program at MI Terpadu Al Madani Margorejo Pati, as well as its supporting and inhibiting factors. The study employs a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The findings indicate that the implementation strategy of the Pocil Program involves careful planning, collaboration with Polsek Margorejo, comprehensive socialization, and program execution under professional supervision. The materials provided include marching drills (PBB), patriotism, and national insight. The program evaluation is conducted annually at the end of the academic year by Polsek Margorejo. The supporting factors include facilities and dedicated time provided by the school. Meanwhile, the inhibiting factors include time constraints from Polsek Margorejo and schedule conflicts with other activities.